Implementasi Penguatan Hak Anak dalam Mewujudkan Ketahanan Pangan Keluarga di Kecamatan Curug Kota Serang - Yeni Widyastuti; Listyaningsih Listyaningsih; Gandung Ismanto (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2020)
Sustainable Development Goals (SDGs) recognize children as agents of change and torch-bearers for sustainable development. So investing in children and young people is very important where the population of children in Indonesia reaches 84 million people or one third of the population of Indonesia (SDGs for Children Annual Reports, UNICEF & Bappenas, 2017). This research was conducted through a quantitative approach and showed the results that the implementation of strengthening children's rights in realizing family food security obtained an average of 2.81 or included in the Good category. The implementation of the family food security program is mainly focused on strengthening children's participation in implementing this program, seen from 3 indicators including (a) Indicators of whether or not this program was carried out or carried out had the highest score of 3.44 or included in the excellent category(b) The ability of the policy to structure implementation properly. get an average value of 2.96 or enter into a good category. (c) Other variables outside the policy that affect the implementation process of the Family Food Security program called KRPL (Sustainable Food Home Area also determines the participation of children in its implementation. In this indicator the value the average given by respondents was 2.04 in the good category. Research recommendations are (a) Forming a group of children (children's forums) that focus on the activities of the Sustainable Food Home Area program so that family food security can be optimally realized (b) Establishing spots or water sources around the food plants worked on by the children's forum to facilitate for children doing plant maintenance activities. Since children find it difficult to get water to water and care for their plants. (C) The local government through the UPT Department of Education and the Department of Agriculture coordinate to provide regular counseling at each school, especially on children's perceptions that children must be actively involved in this program.*Keyword: Family Food Security, Implementation, Rights of the Children